The importance of vaccination in achieving a positive trend in the prevention and treatment of paratyphs in the practice of infectious diseases. (Journal of Universal Science Research, 2024)
Although measures for the treatment of typhoid and paratyphoid, which are considered important and relevant in medical practice today, have been improved, the main measure to combat the disease is vaccination. This presented article provides an analysis of the importance, importance and relevance of the vaccine specifically in the prevention of typhoid and paratyphoid. And the main purpose of this presented work is to outline the importance of vaccination and a brief analysis of modern approaches to the prevention of typhoid and paratyphoid. To date, a number of research projects are underway to introduce various generations of vaccines into practice. However, no matter how high the activity of the vaccine is, it requires sufficient knowledge of the specifics of indications for use, contraindications to use and side effects. Thus, over the past hundred years, preventive vaccination has significantly reduced the incidence and mortality from infectious diseases worldwide. This process is regulated by the national schedule of routine vaccination in all countries. All children should be able to reach their full potential in health and well-being, and no child should die from preventable causes.